Aging resistance, mechanical properties and translucency of different yttria-stabilized zirconia ceramics for monolithic dental crown applications. Issue 6 (June 2018) - Camposilvan, E.; Leone, R.; Gremillard, L.; Sorrentino, R.; Zarone, F.; Ferrari, M.; Chevalier, J.
Abstract: Objectives: The dental market moves towards high-translucency monolithic zirconia dental crowns, which are usually placed either with – or without – a thin glaze layer. The microstructural features and the mechanical performances of these materials are still controversial, as well as their susceptibility to aging. This paper aims at studying these aspects in the current generation of zirconia dental crowns showing different degrees of translucency. Methods: Four different commercial zirconia materials were investigated, including one standard 'full-strength' 3Y-TZP and three grades with improved translucency. The microstructural features (phase composition and assemblage, grain size) were carefully studied, as well as mechanical properties (biaxial bending strength and indentation toughness), translucency and aging behavior (in autoclave at 134 °C). Aging was conducted on crowns with and without glaze to better represent clinical uses. Results: Important differences are found in terms of microstructures among the materials in terms of cubic phase content and yttria in the tetragonal phase, leading to different optical, mechanical and aging resistance properties. We show that higher cubic phase content leads to better translucency and stability in water steam, but at the expense of strength and toughness. A compromise is always inevitable between translucency and aging resistance on one side and mechanical properties on the other side. Significance: - Even so called 'high translucent' zirconia ceramics tested in this work should be considered as medium translucency materials. - Aging occurs in standard state-of-the-art dental zirconia and glazing does not fully avoid this issue. However, aging did not compromise strength even after prolonged duration. - Aging is null in the 'highly translucent' zirconia grades but at the expense of strength, which is then comparable to glass-ceramics.